DOPPLER STATION FOR ORBITAL TRACKING OF LOW-ORBIT SPACECRAFTS BY THEIR RADIO BEACON SIGNALS - Bushuev, F.; Kaliuzhnyi, M.; Khalaley, M.; Kryuchkovskiy, V.; Kulichenko, M.; Shulga, O. (Одеські астрономічні публікації, 2018)
A ground station of orbital tracking of low-orbit spacecrafts has been developed and tested in the RI "Mykolaiv Astronomical Observatory". The station uses the Doppler shift of frequencies of signals radiated by spacecraft radio beacons for their orbital tracking. The station consists of: 1) 10-section antenna with a circular directional diagram and the operating frequency band 400-450 MHz, 2) electronic unit of connection of the antenna sections to a receiver, 3) the SDR-receiver used USB receiver of terrestrial digital TV and radio (“DVB-T+DAB+FM”), 4) personal computer. Software of the station includes the free program HDSDR for SDR-receiver control, as well as an antenna direction control program, a program for determining a frequency of a signal, emitted by satellite radio beacon and received by the station, and a program for clarifying elements of satellite’s orbit using the measured values of the frequency. The NORAD ID of a satellite and a frequency of the signal emitted by its radio beacon should be set to clarify the satellite orbit. The antenna direction control program download current TLE (Two Line Elements) orbital elements of the satellite from the space-track.org site using the satellite’s ID. These elements are used by the program to calculate, as functions of time, the values of range, azimuth and elevation angle of the satellite relative to the station. The program determines then the moments of the connections of the necessary antenna sections to the receiver, and performs these connections in the automatic mode, which provides continuous tracking of the satellite during its passage in the zone of direct radio visibility of the station. Simultaneous recording of the received radio signal is performed by the HDSDR program in wav-files. The program of determining a frequency of satellite radio beacon signal analyzes the records and automatically detects the radio beacon signal and determines its frequency. The initial orbital elements obtained from the space-track site are clarified according to the measured values of the frequency using the program developed by V.A.Yamnitsky. The report presents the results of the station test, which include an estimation of internal errors of the orbital elements determining of tracked satellites. A network of stations similar to the one considered in the report could be used to orbital tracking of low-orbit spacecrafts equipped with radio beacons.